A Novel Photoplethysmograph Sensor Probe Design For Motion Artifact Detection: A Comparison Study With Three Axis Accelerometer - Muhideen Abbas, Hasan; Fahmi, Samsuri; Gan, Kok Beng (JATIT, 2016)
Photoplethysmography (PPG) sensors have become widespread in most of the healthcare categories; its drawback is unreliable during non-stationary states. Adaptive noise cancellation is one of the several techniques have existed to address this issue. The problem of implementing this method still lacks for total detection of induced noise due to the motion. In this work, a new method was introduced for noise detection based on novel PPG sensor probe design by adding a covered photodetector (CPD) as a motion artifact reflector, in addition to the main photodetector (MPD). Experiments of several motion kinds were executed to the tied (CPD) with the accelerometer. Data analysis for the collected signals showed a lengthy convergence between the amplitude fluctuations in the time domain. The CPD precisely indicated all the fundamental frequencies of various induced noise, unlike the accelerometer. Using these photodetectors, the CPD as noise reflector and the MPD to track the contaminated PPG signal is more reliability than other approaches. Implementing this method ensures a high-level accuracy and reducing the cost of repeated false examinations. Furthermore, simple software computation and low power consumption. Practical application of this study will be presented in our next work.